πNN vertex function in a meson-theoretical model - Böckmann, Rainer; et al. (Physical Review C - Nuclear Physics, 1999)
The πNN vertex function is calculated within a dispersion theoretical approach, including both πρ and πσ intermediate states, where the σ meson is an abbreviation for a correlated pion pair in a relative S wave with isospin I = 0. A strong coupling between the πσ and πρ states is found. This leads to a softening of the πNN form factor. In a monopole parametrization, a cutoff Λ ≈ 800 MeV is obtained as compared to Λ ≈ 1000 MeV using πρ intermediate states only.